Reproductive health and birth practices among early married females: A cross-sectional study in Jaipur India - Chaudhary, Chintu; Khan, Mohd. Najmul Aqib; Ahmad, Sameena (Asian Journal of Medical Sciences, 2022)
Background: Early marriage is not only a violation of females but also causes harm to their physical and psychological health. Aims and Objectives: The aim of the study was to determine the prevalence of early marriage and its association with reproductive health of females. Materials and Methods: This community based cross-sectional study was conducted among 322 married females in the field practice areas of JNU-IMRC, Jaipur, Rajasthan. The data were analyzed using Statistical Package for the Social Sciences 20.0. Results: The study found that 53.4% of the females had married before the age of 18 years. Significant associations were found between age at marriage, their socio-economic status, number of children, awareness of contraception, and history of various obstetric complications (P<0.05). Conclusion: The study brings forth the fact that early marriages have an adverse effect on reproductive health of the females. Rigorous efforts and policies should be put in place for the adolescents to understand their reproductive health better.